Design estratégico de moda: princípios metodológicos de cenários futuros de pesquisa de tendências para marcas de moda - Sukiennik, Alice Bittencourt (Universidade do Vale do Rio dos Sinos, 2023)
Fashion goes beyond wearable artifacts, symbolizing expressions of the subject and behavioral representations. By approaching Strategic Design, a proposal that highlights a design activity that exceeds operational techniques, thinking about interfaces between the company, the market and society, it is understood that fashion can be enhanced with spaces for reflection. Future scenarios, in design, are understood as the fabulation dynamics of alternative panoramas to reality, in order to stimulate human innovative and creative capacity. Such narratives of the future can be associated with a practice that is already familiar to the fashion system: the trend research, a process that analyzes emerging movements in the socio-cultural system, interpreting them into possible patterns for fashion and its products. In view of this, and seeking to develop a culture of reflection on the future in fashion, the objective of this work is to develop a proposal of methodological principles for future scenarios and trend research for fashion brands. For this purpose, in addition to the bibliographical research carried out, in-depth interviews with specialists were used, the development of a workshop for the creation of objective methodological principles, and finally, a focus group for the analysis of the results obtained. In general, the contributions that this research brought, in addition to the guidelines developed with the specialists, is the expansion of the understanding of reflection on the future within fashion, understanding it as a potential for an open, accessible and collaborative methodological culture, instigating that the fashion market is attentive to emerging behaviors, which are reflected in its projects and creative collections, in addition to being able to create future possibilities for fashion.
Keywords: Moda; Pesquisa de tendências; Cenários futuros; Design estratégico; Fashion; Trend research; Future scenarios; Strategic design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial